Ethan Allen papers - Allen, Ethan, 1796-1879.
Notes compiled by Allen from various sources relating to the history (1630-1874) and administration of Anglican (later Episcopal) parishes in Maryland, including the parishes of St. James in Anne Arundel County, St. John in Baltimore and Harford counties, Queen Anne, St. John, and St. Paul in Prince Georges County, William and Mary, King and Queen, St. Andrew, and All Faith in Saint Marys County, and the parish of Washington in Washington, D.C. Includes manuscript volume (1860, circa 300 pages) relating to the work (1767-1816) of Thomas John Claggett, first bishop of the Episcopal Church of Maryland, and a compilation entitled "Synodalia" (1864) of records of meetings (1695-1773) of the clergy in Maryland.
In part, typescripts and negative photocopies.
Originals in possession of Henry J. Berkley.
Episcopal clergyman, of Maryland.
Collection material in English.
Keywords: Claggett, Thomas John; All Faith Parish (Saint Marys County, Md.); Church of England -- Maryland; Church of England -- Washington (D.C.); Episcopal Church -- Maryland; Episcopal Church -- Washington (D.C.); King and Queen Parish (Saint Marys County, Md.); Queen Anne Parish (Prince Georges County, Md.); Saint Andrew Parish (Saint Marys County, Md.); Saint James Parish (Anne Arundel County, Md.); Saint John Parish (Baltimore and Harford Counties, Md.); Saint John Parish (Prince Georges County, Md.); Saint Paul Parish (Prince Georges County, Md.); Washington Parish (Washington, D.C.); William and Mary Parish (Saint Marys County, Md.); Maryland -- Church history; Washington (D.C.) -- Church history; Clergy